Multislice CT Virtual Intravascular Endoscopy for Assessing Pulmonary Embolisms: A Pictorial Review - Sun, Zhonghua; Al Dosari, S.; Ng, Curtise; Al-Mumntshari, A.; Almaliky, S. (Korean Radiological Society, 2010)
Multislice CT has been widely used in clinical practice for diagnosing cardiovasculardisease due to its reduced invasiveness and its high spatial and temporalresolution. As a reliable alternative to conventional pulmonary angiography, multisliceCT angiography has been recognized as the first line technique for detectingand diagnosing pulmonary embolism. A pulmonary embolism located in the mainpulmonary artery, as well as being located in the segmental branches, can beaccurately detected with multislice CT imaging, and especially with the use of 16-and 64-slice CT scanners. Visualization of pulmonary embolisms has traditionallybeen limited to 2D, multiplanar reformation and the 3D external surface visualizations.In this pictorial review, we present our experience of using 3D virtualintravascular endoscopy (VIE) to characterize and evaluate the intraluminalappearance of pulmonary embolisms in a group of patients who were suspectedof having pulmonary embolism and who were undergoing multislice CT angiography.We expect that the research findings from this study will provide insight intothe extent of disease and the luminal changes to the pulmonary arteries that aredue to the presence of thrombus, and so monitoring of the progress of diseaseand predicting the treatment outcome can well be achieved.